1997
DOI: 10.1116/1.580735
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of defect levels in chemically deposited CdS films in the cubic-to-hexagonal phase transition

Abstract: Spectral photoconductivity, photoconductive quenching, photoluminescence, and thermally stimulated current measurements, have been carried out in order to study the evolution of defect energy levels in CdS thin films, grown in cubic phase by chemical bath deposition, as a function of thermal annealing temperatures in Ar+S2 atmosphere. The results are influenced by a cubic-to-hexagonal phase transition. From those measurements, a number of trap levels and deep levels in the forbidden band are determined. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 0 publications
3
69
0
Order By: Relevance
“…18 We have not found other PL bands which have been sometimes reported, generally placed at lower energies, which should indicate another type of defect such as cadmium or sulphur vacancies, interstitial cadmium, etc., confirming the semiconductor quality. 16 The transmission ͑dotted line͒ shows the dip due to the ͑111͒ planes in addition to the semiconductor band edge.…”
Section: ͓S0003-6951͑98͒01939-1͔mentioning
confidence: 90%
“…18 We have not found other PL bands which have been sometimes reported, generally placed at lower energies, which should indicate another type of defect such as cadmium or sulphur vacancies, interstitial cadmium, etc., confirming the semiconductor quality. 16 The transmission ͑dotted line͒ shows the dip due to the ͑111͒ planes in addition to the semiconductor band edge.…”
Section: ͓S0003-6951͑98͒01939-1͔mentioning
confidence: 90%
“…[41][42][43][44][45][46] Depending on the growth method and CdS grain size the red luminescence is found centered at 1.67, 44 43,46 It is believed that the red luminescence is caused by transitions of electrons trapped in surface states to the valence band, 39,40 and this effect is therefore correlated with the accumulation of crystallographic defects in CdS layers grown at low deposition temperatures. Annealing of smallgrained CdS films increases grain size, decreases the number of grain boundaries, heals lattice defects, and reduces strain in the layer.…”
Section: -5mentioning
confidence: 99%
“…The peak at 537 nm can be attributed to the presence of sulfur species on the surface of the sample [25]. Vigil et al [27] observed a similar peak at 544 nm which they attributed to sulfur interstitial acceptors I − s compensated by a close ionized donor center. The PL peak observed at 573 nm corresponds to radiative recombination involving shallow levels in the band gap due to native impurities.…”
Section: Resultsmentioning
confidence: 61%
“…The emission peaks at 585 nm and 594 nm are due to deexcitation of electron via the surface/defect states present in the films. The electrons, after excitation across the band edge, are transferred nonradiatively to the surface states extending into the band gap region [27]. The peak observed at 594 nm is discussed in the literature as a donor-acceptor pair (DAP) [28].…”
Section: Resultsmentioning
confidence: 99%